2018
DOI: 10.1124/mol.117.110114
|View full text |Cite
|
Sign up to set email alerts
|

Differential Pharmacology and Binding of mGlu2 Receptor Allosteric Modulators

Abstract: Allosteric modulation of metabotropic glutamate receptor 2 (mGlu) has demonstrated efficacy in preclinical rodent models of several brain disorders, leading to industry and academic drug discovery efforts. Although the pharmacology and binding sites of some mGlu allosteric modulators have been characterized previously, questions remain about the nature of the allosteric mechanism of cooperativity with glutamate and whether structurally diverse allosteric modulators bind in an identical manner to specific allos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 51 publications
1
56
0
Order By: Relevance
“…In contrast, removal of the extracellular domains shifted the dose–response curve to the left, consistent with a model where the LBD provides tonic inhibition of TMD activation by PAMs that is relieved either by LBD closure or by removal of the ECD. Further supporting this model, binding studies have shown up to a 10-fold leftward shift in PAM binding to mGluR2 in the presence of glutamate (Doornbos et al, 2016; O'Brien et al, 2018). Despite the modulatory effects of the LBD on PAM activation, saturating concentrations of LY48 were unable to directly induce LBD closure as assayed using an inter-LBD FRET assay (Figure 1—figure supplement 3).…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…In contrast, removal of the extracellular domains shifted the dose–response curve to the left, consistent with a model where the LBD provides tonic inhibition of TMD activation by PAMs that is relieved either by LBD closure or by removal of the ECD. Further supporting this model, binding studies have shown up to a 10-fold leftward shift in PAM binding to mGluR2 in the presence of glutamate (Doornbos et al, 2016; O'Brien et al, 2018). Despite the modulatory effects of the LBD on PAM activation, saturating concentrations of LY48 were unable to directly induce LBD closure as assayed using an inter-LBD FRET assay (Figure 1—figure supplement 3).…”
Section: Resultsmentioning
confidence: 71%
“…Classically, positive allosteric modulators (PAMs) of GPCRs have been defined by their ability to amplify the effects of orthosteric compounds without directly activating the receptor (May et al, 2007) (Lindsley et al, 2016; Wacker et al, 2017). However, some studies have shown both modulation and direct activation of GPCRs by PAMs (May et al, 2007), including mGluRs (Rovira et al, 2015) (O'Brien et al, 2018). Most previous studies, however, relied on end-point assays and thereby failed to provide dynamic information about the onset and reversibility of PAM effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are multiple examples of allosteric modulators of GPCRs inducing biased signaling, little is known about the structural basis of biased versus non-biased signaling. Previous studies reveal multiple allosteric binding sites for some GPCRs, which could contribute to different responses to distinct classes of allosteric modulators (70)(71)(72). However, recent studies suggest that differences in M1 PAM functionality may not be due to binding to different allosteric binding pockets, but that binding of PAMs to a single allosteric site may stabilize different receptor conformational states (73,74).…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that distinct chemotypes interacting allosterically with the mGluRs bind to the same binding site and displace each other is not warranted. Studies have shown that very minor differences in the structure of a drug and a radioligand can lead to unexpected results [74,75]. It has been recommended to de-risk such assumption by conducting the appropriate in vitro tests and confirm competitive behaviors for the pair drug-radioligand to be used in vivo in subsequent studies [74,75].…”
Section: Preclinical Efficacy Studiesmentioning
confidence: 99%